Serious Adverse Drug Reactions to Antipsychotics in Minors with Multiple Disabilities: Preventability and Potential Cost Savings by Therapeutic Drug Monitoring - Fekete, Stefanie; Guentzel, Tim; Egberts, Karin; Geissler, Julia; Neubert, Antje; Gerlach, Manfred; Romanos, Marcel; Taurines, Regina (Pharmacopsychiatry, 2022)
Introduction Children and adolescents with multiple disabilities and mental disorders (CAMD) are frequently treated with antipsychotic drugs. However, CAMD are particularly susceptible to serious adverse drug reactions (sADRs). This retrospective study examined the frequency of sADRs to antipsychotics in CAMD. Further, the potential preventability of these sADRs through therapeutic drug monitoring (TDM) and the potential socio-economic benefits of TDM were explored.Methods Routine clinical data of all patients treated at a specialized psychiatric clinic for CAMD between January 2017 and December 2018 were retrospectively examined. Data on the occurrence of sADRs (definition according to the European Medicines Agency), their causality with antipsychotics, as well as their preventability (Schumock criteria) were extracted from patient files. The prolongation of the hospital stay due to sADRs was calculated, and the cost savings were estimated if TDM had been applied. The data were based on a subsample of the KiDSafe project, supported by the Innovation Fund of the Joint Federal Committee, grant number 01NVF16021.Results One hundred two CAMD who were administered at least one antipsychotic drug during inpatient treatment were identified. Of these patients, 22 (21.6%) sADRs with a possible causal relationship with the antipsychotic treatment were documented. Eleven sADRs (50%) could potentially have been prevented through TDM. Mitigating sADRs through TDM likely would have prevented prolonged hospital stays and thus conferred considerable savings for health insurance companies.Discussion The routine implementation of TDM is urgently recommended for antipsychotic treatment in CAMD to increase drug therapy safety.
CRIS-Team WoS Importer:2022-11-25